Consumer interest protection in unfair competition in the digital economy ERA - Liu, Fang; Li, Zichen (Edelweiss Applied Science and Technology, 2025)
This study explores the protection of consumer interests in the context of unfair competition in the digital economy. With the rapid development of digital technology, the role and status of consumers in the market have changed significantly, and consumers are not only the receivers of goods and services but also the suppliers of new production factors. However, operators’ unfair competition behaviors, such as algorithmic manipulation and big data exploitation, have seriously damaged consumers’ rights to know, choose, and welfare. This study analyzes the transformation of unfair competition behavior and its causes, points out the deficiencies of the current law in the protection of consumer interests, and proposes a transformation path from passive protection to active protection, indirect protection to direct protection, and individual protection to collective protection. Finally, this paper offers suggestions on system construction from three aspects: perfecting legal rules, strengthening judicial protection, and optimizing auxiliary mechanisms, in order to comprehensively enhance the protection of consumer interests.